Cas9/sgRNA-based genome editing and other reverse genetic approaches for functional genomic studies in rice. (22nd March 2018) - Moin, Mazahar; Bakshi, Achala; Madhav, M S; Kirti, P B
Abstract: One of the important and direct ways of investigating the function of a gene is to characterize the phenotypic consequences associated with loss or gain-of-function of the corresponding gene. These mutagenesis strategies have been successfully deployed in Arabidopsis, and subsequently extended to crop species including rice. Researchers have made vast advancements in the area of rice genomics and functional genomics, as it is a diploid plant with a relatively smaller genome size unlike other cereals. The advent of rice genome research and the annotation of high-quality genome sequencing along with the developments in databases and computer searches have enabled the functional characterization of unknown genes in rice. Further, with the improvements in the efficiency of regeneration and transformation protocols, it has now become feasible to produce sizable mutant populations in indica rice varieties also. In this review, various mutagenesis methods, the current status of the mutant resources, limitations and strengths of insertional mutagenesis approaches and also results obtained with suitable screens for stress tolerance in rice are discussed. In addition, targeted genome editing using clustered regularly interspaced short palindromic repeats (CRISPR)/CRISPR-associated protein 9 (Cas9) or Cas9/single-guide RNA system and its potential applications in generating transgene-free rice plants through genome engineering as an efficient alternative to classical transgenic technology are also discussed.